Bortezomib‐induced sensitization of malignant human glioma cells to vorinostat‐induced apoptosis depends on reactive oxygen species production, mitochondrial dysfunction, Noxa upregulation, Mcl‐1 cleavage, and DNA damage1. Issue 2 (15th November 2011) - Premkumar, Daniel R.; Jane, Esther P.; Agostino, Naomi R.; DiDomenico, Joseph D.; Pollack, Ian F.
Abstract Glioblastomas are invasive tumors with poor prognosis despite current therapies. Histone deacetylase inhibitors (HDACIs) represent a class of agents that can modulate gene expression to reduce tumor growth, and we and others have noted some antiglioma activity from HDACIs, such as vorinostat, although insufficient to warrant use as monotherapy. We have recently demonstrated that proteasome inhibitors, such as bortezomib, dramatically sensitized highly resistant glioma cells to apoptosis induction, suggesting that proteasomal inhibition may be a promising combination strategy for glioma therapeutics. In this study, we examined whether bortezomib could enhance response to HDAC inhibition in glioma cells. Although primary cells from glioblastoma multiforme (GBM) patients and established glioma cell lines did not show significant induction of apoptosis with vorinostat treatment alone, the combination of vorinostat plus bortezomib significantly enhanced apoptosis. The enhanced efficacy was due to proapoptotic mitochondrial injury and increased generation of reactive oxygen species. Our results also revealed that combination of bortezomib with vorinostat enhanced apoptosis by increasing Mcl‐1 cleavage, Noxa upregulation, Bak and Bax activation, and cytochrome c release. Further downregulation of Mcl‐1 using shRNA enhanced cell killing by the bortezomib/vorinostat combination. Vorinostat induced a rapid and sustained phosphorylation of histone H2AX in primary GBM and T98G cells, and this effect was significantly enhanced by co‐administration of bortezomib. Vorinostat/bortezomib combination also induced Rad51 downregulation, which plays an important role in the synergistic enhancement of DNA damage and apoptosis. The significantly enhanced antitumor activity that results from the combination of bortezomib and HDACIs offers promise as a novel treatment for glioma patients. © 2011 Wiley Periodicals, Inc.